2014
DOI: 10.1111/mec.13019
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus‐induced tree‐top disease: how extended is the role ofegtas a gene for the extended phenotype?

Abstract: Many parasites alter host behaviour to enhance their chance of transmission. Recently, the ecdysteroid UDP-glucosyl transferase (egt) gene from the baculovirus Lymantria dispar multiple nucleopolyhedrovirus (LdMNPV) was identified to induce tree-top disease in L. dispar larvae. Infected gypsy moth larvae died at elevated positions (hence the term tree-top disease), which is thought to promote dissemination of the virus to lower foliage. It is, however, unknown whether egt has a conserved role among baculovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(105 citation statements)
references
References 40 publications
1
102
1
Order By: Relevance
“…It was hypothesized that inactivation of 20E by egt disrupts the moulting cycle, inducing larvae to remain up in the tree in a feeding state, rather than crawling down to moult. Upon infection with an egt deletion virus, larvae stop feeding and might move down to moult (Hoover et al., ; Ros et al., ). A similar effect of egt on moulting‐related behaviour was seen in AcMNPV‐infected S. exigua and T. ni larvae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was hypothesized that inactivation of 20E by egt disrupts the moulting cycle, inducing larvae to remain up in the tree in a feeding state, rather than crawling down to moult. Upon infection with an egt deletion virus, larvae stop feeding and might move down to moult (Hoover et al., ; Ros et al., ). A similar effect of egt on moulting‐related behaviour was seen in AcMNPV‐infected S. exigua and T. ni larvae.…”
Section: Discussionmentioning
confidence: 99%
“…These larvae normally climb to lower positions prior to moulting, and this behaviour was absent in WT AcMNPV‐infected larvae. However, in AcMNPV‐infected S. exigua and T. ni larvae, death occurred long after moulting, and climbing prior to death (tree‐top disease), which occurs at a later stage of infection, was not affected by egt (Ros et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstrating that pathogen-induced behavioural changes are adaptive and do increase transmission can be challenging. However, it has recently been demonstrated that the egt gene is not responsible for the climbing behaviour seen when the cabbage looper, Trichoplusia ni and S. exigua are infected by AcMNPV [27]. Research on the domesticated silkworm, Bombyx mori, showed that the protein tyrosine phosphatase (ptp) gene of its NPV was responsible for the hyperactivity of infected larvae [23].…”
Section: Pathogen-induced Changes In Transmission Behaviourmentioning
confidence: 99%
“…As ptp deletion affects ELA but not climbing height during AcMNPV infection, ELA and 60 CB are thought to be governed by different mechanisms [12]. The deletion of egt in Lymantria dispar 61 multiple nucleopolyhedrovirus and Spodoptera exigua multiple nucleopolyhedrovirus mitigates the 62 climbing height of Lymantria dispar and S. exigua larvae, respectively, although the enhancement of 63 larval activity by egt was not observed in BmNPV-and AcMNPV-infected larvae [9,[13][14][15]. A recent 64 study further showed that miRNA-mediated hormonal regulation affects the climbing height of 65…”
mentioning
confidence: 99%